NEETs in a rural region of Southern Europe: perceived self-efficacy, perceived barriers, educational expectations, and vocational expectations - Simões, F. (2017)
The aim of this research is to understand the influence of demographic and professional experience factors on the self-efficacy and perceived barriers of rural Portuguese youths not in employment, education or training (NEET), as well as on their educational and vocational expectations at age 35. These indicators are involved in the compromise mechanism of choice of the circumscription and compromise theory, a construct that describes the reason why certain vocational alternatives are progressively restricted among young adults. Most of the participants (n?=?137) were female (62%) and their age ranged from 18 to 30 (M?=?24.88; SD?=?2.30). Findings show that the participants' self-efficacy was positively affected by having a previous job contract, and negatively influenced by longer unemployment periods (>24 months). Longer unemployment periods also increase the perception of barriers. Educational expectations at age 35 were significantly higher among participants who had completed middle school and marginally lower for those living with their parents, while vocational expectations at age 35 were more conservative among those who had concluded high school. Recommendations are made regarding employment policies as well as training and vocational guidance interventions for NEETs in rural regions.